Pertumbuhan dan Produksi Jamur Lentinus sajor-caju isolat LSC9 pada Media Serbuk Gergajian Kayu Sengon (Paraserianthes falcataria) dan Tandan Kosong Kelapa Sawit - SULISTANY, HENNY; SUDIRMAN, LISDAR IDWAN (Jurnal Sumberdaya Hayati, 2016)
Paraserianthes falcataria sawdust (SGS) and oil palm empty fruit bunch (TKKS) are by-product of forestry and oil palm industries. SGS is commonly substrates for mushroom cultivation. TKKS is expected to be an alternative substrates for mushroom cultivation besides SGS. This study was conducted to determine the growth and fruiting body production of Lentinus sajor-caju LSC9 isolate on SGS, TKKS and mixtures of both substrates (C) with proportion 1:1 respectively. Each substrates were added with 15% rice bran, 1.5% gypsum and 1.5% CaCO3 with a total weight of 500 g/bag. The result showed that the growth and fruiting body production of Lentinus sajor-caju LSC9 isolate on SGS was better than TKKS and C substrates with biological efficiency on SGS substrates (50.88%) higher than TKKS substrates (34.42%) and C substrates (29.51%), with vegetative phase (16 days), generative phase (100 days) and growth and development phase (115 days) on TKKS substrates were shorter than SGS and C substrates. The greatest pileus number found on SGS substrates (12 pieces), while the largest pileus diameter found on C substrates (10.17 cm). Nevertheless, TKKS can be used as alternative substrates for fruiting body production of Lentinus sajor-caju LSC9 isolate.